A Critical Review of Recent Papers in Educational Games for Early Childhood: Challenges and Future Prospects - Roza, Roza Novita; Dwiningrum, Siti Irene Astuti (Program Studi Magister Pendidikan Anak Usia Dini, 2025)
This paper critically reviews the latest literature in the field of educational games for early childhood, with a focus on the challenges faced and future prospects. Educational games for early childhood have experienced significant development, becoming an important tool in increasing motivation and learning effectiveness. However, challenges such as technological limitations, inadequate game design, and lack of integration with educational curricula remain major obstacles. Through analysis of recent research, this paper identifies strategies that can overcome these challenges and explores potential future developments. The review results show that with continuously developing technological innovations, multidisciplinary collaboration, and student-centered approaches, educational games have bright prospects in creating more interactive and effective learning experiences. This paper provides valuable insights for researchers, educators, and game developers in designing and implementing better educational games in the future.